2016
DOI: 10.33549/physiolres.933402
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Red Blood Cell Deformability and Na,K-ATPase Function in Selected Risk Factors of Cardiovascular Diseases in Humans: Focus on Hypertension, Diabetes Mellitus and Hypercholesterolemia

Abstract: Deformability of red blood cells (RBC) is the ability of RBC to change their shape in order to pass through narrow capillaries in circulation. Deterioration in deformability of RBC contributes to alterations in microcirculatory blood flow and delivery of oxygen to tissues. Several factors are responsible for maintenance of RBC deformability. One of them is the Na,K-ATPase known as crucial enzyme in maintenance of intracellular ionic homeostasis affecting thus regulation of cellular volume and consequently RBC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 78 publications
5
53
0
3
Order By: Relevance
“…Besides, plasma NO increases RBC velocity through microvascular beds in vivo by regulating vascular tone and modifying RBC deformability . Importantly, RBC deformability may affect microcirculatory blood flow and oxygen delivery to tissues, and impaired RBC deformability independently predicts adverse outcomes in cardiovascular diseases and sepsis . Our results indicated that high‐dose NTG may benefit tissue perfusion of cardiac surgical patients through improving RBC deformability and function of cytoskeletal structural proteins during CPB.…”
Section: Discussionmentioning
confidence: 74%
“…Besides, plasma NO increases RBC velocity through microvascular beds in vivo by regulating vascular tone and modifying RBC deformability . Importantly, RBC deformability may affect microcirculatory blood flow and oxygen delivery to tissues, and impaired RBC deformability independently predicts adverse outcomes in cardiovascular diseases and sepsis . Our results indicated that high‐dose NTG may benefit tissue perfusion of cardiac surgical patients through improving RBC deformability and function of cytoskeletal structural proteins during CPB.…”
Section: Discussionmentioning
confidence: 74%
“…Показано, что прогрессирование ряда заболеваний сопровождается морфофункциональными изменениями форменных элементов крови, в том числе, эритроцитов [26]. Более поздние исследования позволили предположить, что нарушение функционального состояния эритроцитов (изменение их деформируемости) можно рассматривать как один из патогенетических механизмов развития МС [27].…”
Section: функциональные свойства эритроцитовunclassified
“…The mechanical analysis of a cell population, such as a blood sample, enables meaningful biological and medical interpretation for diagnosis and monitoring of diseases. Malaria, [10][11][12] diabetes, 13,14 hypercholesterolemia 14,15 and many others are examples of widespread blood diseases that alter the mechanics of human erythrocytes also called red blood cells (RBCs). 16,17 Most methods for mechanical analysis provide number averaged values such as the blood's viscosity.…”
Section: Introductionmentioning
confidence: 99%